Positive Word of Positive Word of Mouth for Supply Chain Management create a Psychological effect which increases the Intention to Purchase among Indonesian Electronic Industry - Wiewiek Indriani; Satria Bangsawan; Mahrinasari MS (International Journal of Supply Chain Management, 2020)
Purpose of this study is to investigate the effect of positive word of mouth (PWM) for supply chain on intention to purchase in Indonesian electronic industry. Literature ignore the Indonesian electronic industry in respect to the relationship between PWM for supply chain and intention to purchase. Population of the study was the Indonesian electronic companies. A survey was used for data collection through questionnaire. 7-point Likert scale was utilized in this study. By using the area cluster sampling, 400 questionnaires were distributed, and data were collected from customers of electronic companies. Results of the study highlighted that psychological effect of PWM has significant effect on intention to purchase through product image. PWM for supply chain has no direct effect on intention to purchase. It has indirect effect with the help of product image. Product image transfer the positive effect of PWM on intention to purchase among Indonesian electronic companies. Additionally, it is found that PWM for supply chain has positive effect on product image and customer perception. Moreover, product image has positive effect on intention to purchase. However, customer perception has no effect on intention to purchase.